2017
DOI: 10.1016/j.jsat.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a technology-based, integrated smoking cessation and alcohol intervention for smoking cessation in adolescents: Results of a cluster-randomised controlled trial

Abstract: Overall, the integrated smoking cessation and alcohol intervention exhibited no advantages over a smoking cessation only intervention, but it might be more effective for the subgroup of adolescent smokers with higher alcohol consumption. Providing a combined smoking cessation and alcohol intervention might be recommended for adolescent smokers with higher-level alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Data for this study were extracted from a two-arm, parallel-group, cluster RCT that used school class as the randomization unit, as detailed elsewhere [ 9 , 25 ]. Students in vocational or upper secondary schools in Switzerland were invited to participate in a technology-based program called MobileCoach Tobacco (MCT) if they (1) either smoked on a daily or occasional basis (at least 4 cigarettes in the preceding month and at least one cigarette during the preceding week) and (2) owned a mobile phone .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data for this study were extracted from a two-arm, parallel-group, cluster RCT that used school class as the randomization unit, as detailed elsewhere [ 9 , 25 ]. Students in vocational or upper secondary schools in Switzerland were invited to participate in a technology-based program called MobileCoach Tobacco (MCT) if they (1) either smoked on a daily or occasional basis (at least 4 cigarettes in the preceding month and at least one cigarette during the preceding week) and (2) owned a mobile phone .…”
Section: Methodsmentioning
confidence: 99%
“…They were randomly assigned to either the combined program ( MCT+ , n=730) or to the smoking cessation only program ( MCT , n=741). The original study [ 9 ] found no significant difference between the programs in terms of reducing the number of cigarettes used per day ( MCT+ vs MCT : −2.7 vs −2.8) or in increasing the 7-day point prevalence of smoking abstinence at follow-up ( MCT+ vs MCT : 14.9% vs 14.0%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of students in Switzerland, a 3-month mobile intervention demonstrated no overall beneficial effects for an integrated smoking and alcohol cessation intervention compared to smoking cessation alone. However, participants with highrisk alcohol consumption in the integrated intervention decreased their cigarette use to a much greater extent than those in the single intervention [14]. More research is needed to determine how best to harness digital tools to target tobacco use and HED in young adults.…”
Section: Introductionmentioning
confidence: 98%
“…Almost all tobacco use starts from youth and young adulthood which before age 18 years and is considered as an unsafe action, since the adolescent is a period of great exposure and vulnerability to consumption of tobacco (D'Angelo et al, 2016;Jamal, Gentzke, Hu, Cullen, Apelberg, Homa, & King, 2017;Andrade, Ferreira, Ramos, Ramos, Scarabottolo, Saraiva, Gobbo, & Christofaro, 2017). Low education attainment and socioeconomic level, parental smoking (especially mother), tobacco advertisement or promotion, friends and peers smoking, alcohol use could be the contributing factors for tobacco use of the adolescents (Andrade et al, 2017;Haug, Paz Castro, Kowatsch, Filler, & Schaub, 2017;Xiao, Feng, Jiang, Zhang, & Liu, 2017). Many studies concluded that smoking adolescents suffer from nicotine dependence may have worse performance on standardized tests, poorer physical activity, alcohol abuse and insomnia when comparing with their non-smoking peers (Sabado, Haynie, Gilman, Simons-Morton, & Choi, 2017).…”
Section: Introduction mentioning
confidence: 99%